METER OF WEAK ALTERNATING CURRENTS - Старцев, Володимир; Деревягін, Ярослав; Бекіров, Володимир; Чуднівський, Віктор (SWorldJournal, 2024)
An alternating current meter with a wide dynamic range is described. Expressions are obtained to determine the optimal input resistance providing maximum sensitivity. Expressions defining the parameters of the amplitude characteristics are given.